PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SDN GUGUS V CAKRANEGARA - Susmayati , Susmayati; Zain, M. Irawan; Affandi, Lalu Hamdian (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2019)
This study aims to determine the effect of the inquiry learning model on science learning outcomes of fourth-grade students at SDN Gugus V Cakranegara in the 2019/2020 academic year. This research is a quasi-experimental study using the Nonequivalent Control Group Design. Data were collected using a multiple-choice test. The analysis results show that the t-value (3.226) is greater than the t-table (2.002) at the 5% significance level, indicating that H₀ is rejected and Hₐ is accepted. This suggests a significant difference in learning outcomes between the experimental and control classes. Thus, the inquiry learning model is effective in improving students' science learning outcomes.